Strategic implementation of a web-based business management software with radio frequency identification (RFID) data integration in a new fitness business through scenario building - Salen, Royce Kamille R.
The Philippine fitness industry continues to grow, as more Filipinos become health conscious. Multiple fitness regimens are widespread in the country, and one of them that is currently trending is functional fitness. In the field of functional fitness, CrossFit is probably the most popular one. To date, there are about ten (10) official CrossFIt facilities in the country, majority of which are based in Metro Manila.